Informational Chat-bot for Students and Teachers Based on VK and MOODLE - Bulaev, Alexey; Zhidkov, Alexander (Computer Tools in Education, 2022)
This article presents the implementation of a chatbot for interacting with the Moodle learning system at the teacher-student level using the VK social network. An algorithm for connecting a chatbot to Moodle and VK, a physical model of the chatbot database are proposed. The user roles of the chatbot "administrator" and "student" with their corresponding functions, use-case diagrams and a deployment diagram have been developed. An example of the implementation of a chatbot in Python is given, its interfaces are presented.